Developing Social Interaction Skills with Game Technology - Lidya Oktorina Kusuma Sakti; Septyana Hardianti Yunanto (SISFORMA, 2018)
Socialization is an essential process in human living. Human is a social creature which can not living without the help of others, so human needs friends to communicate and interact with each others to make a living better. Through a socialization, human can build good characters to care with others and theirs social life circle. Nowadays, game technology have already fast and sophisticated. People use game not only for entertainment media but for education media and media to prevent social problems in the society. With game technology, game will be expected to reduce lack of socialization in the society. It can help someone to open his/herself and develop social skill with interacting in social society using social feature in the game.